2016
DOI: 10.1039/c5cc08064a
|View full text |Cite
|
Sign up to set email alerts
|

Nickel sulfide microsphere film on Ni foam as an efficient bifunctional electrocatalyst for overall water splitting

Abstract: Developing low-cost, efficient, and bifunctional electrocatalysts for both the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) is an appealing yet challenging task. Herein, for the first time, a NiS microsphere film was grown in situ on Ni foam (NiS/Ni foam) via a sulfurization reaction as an efficient bifunctional electrocatalyst for overall water splitting with superior activity and good durability. This NiS/Ni foam electrode delivers 20 mA cm(-2) at an overpotential of 158 mV for the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
233
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 506 publications
(253 citation statements)
references
References 37 publications
(46 reference statements)
19
233
1
Order By: Relevance
“…According to the XRD analyses, the CF still comprised a mixture of fcc‐Co and hcp‐Co, but weak broadened diffraction peaks from β‐CoOOH (JCPDS no. 14‐0673) could also be resolved (Figure S14), consistent with previous reports . While for the Co@Co 9 S 8 electrodes, it was found that the particulate morphology disappeared after the extended OER electrolysis, and the surface of both Co@Co 9 S 8 ‐180 and Co@Co 9 S 8 ‐220 became smoother (Figure c and Figure S15 a).…”
Section: Resultssupporting
confidence: 89%
“…According to the XRD analyses, the CF still comprised a mixture of fcc‐Co and hcp‐Co, but weak broadened diffraction peaks from β‐CoOOH (JCPDS no. 14‐0673) could also be resolved (Figure S14), consistent with previous reports . While for the Co@Co 9 S 8 electrodes, it was found that the particulate morphology disappeared after the extended OER electrolysis, and the surface of both Co@Co 9 S 8 ‐180 and Co@Co 9 S 8 ‐220 became smoother (Figure c and Figure S15 a).…”
Section: Resultssupporting
confidence: 89%
“…This high binding energy shift is smaller than the low binding energy shift, around 1 eV, observed for the before and after sulfurization case, implying partial transformation of the MS bonding of the sulfide shell to MO bonding after the stability test. This observation is consistent with the finding previously reported in relevant literature, in which oxyhydroxide thin layers were formed from sulfides after the OER stability test. The formation of the MO bonding, more resistant to the OER than the MS bonding, ensures the outstanding stability of the catalyst.…”
Section: Resultssupporting
confidence: 94%
“…To summarize,as eries of ultrathin MOF-74 nanosheets with abundant coordinatively unsaturated metal sites are synthesized through coordination assisted 2dOSA from their corresponding M-ONS,w hich cannot be obtained from the [39] a-CoSe/ Ti, [40] Co 9 S 8 /NOSC, [41] CoFePO, [42] CoP/NC, [43] CoNiP, [44] Ni-NiP, [44] Ni@NC-800/NF, [45] NiFeO x /CNF, [46] NiMo, [47] NiS/NF, [48] NiSe/NF, [49] N-Ni 3 S 2 -NF, [50] and Ni 5 P 4 . [51] delamination of their bulk counterparts or the conventional solvothermal method.…”
Section: Resultsmentioning
confidence: 99%